Coronavirus Infection Caused by the Omicron Variant and its Daughter Genovariants in Russia (2022–2023) - L. S. Karpova; M. Yu. Pelikh; N. M. Popovtseva; T. P. Stolyarova; K. M. Volik; K. A. Stolyarov (Эпидемиология и вакцинопрофилактика)
Relevance. Surveillance of new genetic variants and manifestations of the epidemic process in SARS-CoV-2 is relevant for predicting the epidemiological situation and timely introduction of anti-epidemic measures. Aim. To evaluate changes in the intensity of the epidemic process during the long circulation of the «omicron» variant and its daughter genovariants. Materials and methods. The analysis of the computer database of the WHO National Center for morbidity, hospitalization and deaths from COVID-19 of the population as a whole and by age groups of 54 cities of the Russian Federation was carried out. Results. Since the appearance of COVID-19 in Russia in 2020, the maximum intensity was the V (winter–spring) wave of 2022. The intensity of the VI (autumn) and VII (winter–spring) waves was lower. In the VI wave, the incidence and mortality from COVID-19 of the population of the RF as a whole decreased by 2.5 and 6.5 times, St. Petersburg – by 2.6 and 29.7 times, and Moscow by 1.6 and 26.6 times. In the VII wave, compared with the VI wave, the decrease in morbidity was less. By age groups, the incidence decreased more among children aged 7–14 years (4.3 times in the VI wave) and less among children 0 –2 and people over 65 years (2.0 times), there was a tendency to increase the proportion of people over 65 years from 18% to 27%. The incidence rates of COVID-19 in the population as a whole and in age groups were higher in 4 FD (North-West, Far East, Siberia and the Center). In 2022, an interepidemic period was revealed for the first time in Russia, the duration of which was in megacities for 9 and FD – from 11 to 13 weeks. In the interepidemic period, the incidence was less than in the minimum VII (winter-spring) wave in the RF as a whole – by 4.6 times, in St. Petersburg – by 7.1 times and in Moscow – by 15 times. There were no deaths among children in the observed cities, and an increase in the total coefficient of mortality rate is associated with mortality among people over 65 years of age. Conclusion. The decrease in the intensity of the epidemicprocess in the VI and VII waves is caused by the prolonged circulation of omicron and its daughter genovarians.